Methods of Preparing Internal Combustion Engine Cylinder Bore Surfaces for Frictional Improvement - Kong, Chung Hwa; D., Ramasamy; K., Kadirgama; M. M., Noor; M. M., Rahman; Samykano, Mahendran (EDP Sciences, 2017)
Frictional losses between the piston rings to cylinder bore surface is one of the major sources of mechanical losses in an internal combustion engine (ICE). Traditional plateau honing produces a relatively rough cylinder bore surface with many valleys for oil retention and plateau surfaces that are usually has micro roughness's that causes mechanical friction to act as a bearing surface. A smooth polished dimpled surface is more ideal to achieve low friction and wear in an ICE. Alternative methods to create a smooth dimpled surface on a hypereutectic aluminum ADC12 substrate for frictional improvements are evaluated in this study using an oscillating wear tester (OWT). The methods include casting in the dimples in the aluminum matrix, sandblasting as well as embossing the pits using a gritted roller. The texture samples are evaluated by examining the surface properties, measuring frictional coefficient as well as wear characteristics. It was found that the samples embossed with #480 grit sandpaper and sandblasted with #240 sieve sand samples had the more desired properties with a reduced coefficient of friction (μ) of 23% at low sliding speeds before hydrodynamic lubrication mode and 6.9% in the fully hydrodynamic lubrication region. Although samples cast with added graphite powder had much lower friction, it had insufficient oil retention volume and resistance against catastrophic wear.